Birds of Aruba, Bonaire, and Curacao : A Site and Field Guide - Wells, Jeffrey V. (Jeffrey Vance), 1964-; Wells, Allison Childs (Book collections on Project MUSE., 2017)
"A site guide and field guide to the birds of Aruba, Bonaire, and Curaçao. Site guide includes maps, directions, photos, and birds likely to be found. Field guide includes illustrations and describes plumage, similar species, vocalizations, status, and range"--